Rh/Cu‐Catalyzed Cascade [4+2] Vinylic C−H O‐Annulation and Ring Contraction of α‐Aryl Enones with Alkynes in Air. Issue 15 (9th March 2017) - Zhao, Yinsong; Li, Shiqing; Zheng, Xuesong; Tang, Junbin; She, Zhijie; Gao, Ge; You, Jingsong
Abstract: An unprecedented Rh‐catalyzed ketone‐directed vinylic C−H activation/[4+2] O ‐annulation of α‐aryl enones with internal alkynes followed by a Cu‐catalyzed ring contraction in air to provide multiaryl‐substituted furan derivatives has been developed. The preliminary mechanism study identifies the active pyrylium salt as the key intermediate. Abstract : First rhodium, then copper : An unprecedented cascade reaction consisting of a Rh‐catalyzed ketone‐directed vinylic C−H [4+2] O ‐annulation of α, β‐enones with alkynes and a subsequent Cu‐catalyzed ring contraction in air to form multiaryl‐substituted furan derivatives is realized. The pyrylium salt is identified as the key intermediate.